2019
DOI: 10.1097/md.0000000000015935
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of incision infection after posterior lumbar surgery in diabetic patients

Abstract: Background: Patients requiring posterior lumbar surgery have increased annually. Incision infection after lumbar surgery has serious consequences for patients. However, data on the related factors of incision infection after lumbar surgery in diabetic patients are limited. Therefore, this study aimed to analyze diabetic patients who underwent lumbar surgery and to explore the risk factors of perioperative incision infection to provide a scientific basis for perioperative intervention of lumbar spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…For patients with diabetes, smoking is a risk factor of postoperative infection. Peng et al 182 proved that smoking is a risk factor for wound infection after lumbar surgery in patients with diabetes (OR=3.830; 95% CI: 1.003-6.684); however, 4 weeks of strict smoking cessation prior to surgery reduced the risk of wound infection. Smoking results in an increased risk of infection at other sites after surgery with a prolonged hospitalization time and increased expenses.…”
Section: Smoking and Surgical Site Infection (Ssi)mentioning
confidence: 99%
“…For patients with diabetes, smoking is a risk factor of postoperative infection. Peng et al 182 proved that smoking is a risk factor for wound infection after lumbar surgery in patients with diabetes (OR=3.830; 95% CI: 1.003-6.684); however, 4 weeks of strict smoking cessation prior to surgery reduced the risk of wound infection. Smoking results in an increased risk of infection at other sites after surgery with a prolonged hospitalization time and increased expenses.…”
Section: Smoking and Surgical Site Infection (Ssi)mentioning
confidence: 99%
“…A more recent study 18 examined a cohort of 523 diabetic patients who underwent posterior lumbar surgery with a wound infection rate of 7.1%. They found that HbA1c 7.50 increased the odds of a wound infection significantly, but did not find a correlation between age or BMI and wound infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…Hwang, J. U. team discovered that hb1c level more than 6.9% would increase the risk of getting SSI [29]. Peng, W. concluded that during 6 years of retrospective study of 523 Diabetes Mellitus patient who went for lumbar surgery, 7.1% got SSI, superficial infection accounted for 4.2% and deep infection made up 2.9% [30]. So preoperative blood glucose level, hb1c level control is strictly required for prevention SSI.…”
Section: Incidencementioning
confidence: 99%
“…Risk factor correlated with SSI. Correlation of the surgical duration with SSI(Kim et al, 2014) 30. days after an operative procedure and involves deep soft tissues of the incision fascial and muscle layers[10].Early diagnosis of surgical site infection can improve the prognosis.…”
mentioning
confidence: 99%